Cytomegalovirus Immunoglobulin G (IgG) Titer and Coronary Artery Disease in People With Human Immunodeficiency Virus (HIV). (17th August 2022) - Schnittman, Samuel R; Lu, Michael T; Mayrhofer, Thomas; Burdo, Tricia H; Fitch, Kathleen V; McCallum, Sara; Fulda, Evelynne S; Zanni, Markella V; Foldyna, Borek; Malvestutto, Carlos; Fichtenbaum, Carl J; Aberg, Judith A; et al.
Abstract: Background: Cytomegalovirus (CMV) infection is thought to result in increased immune activation in people with human immunodeficiency virus (HIV, PWH). Although some data have linked asymptomatic CMV infection to cardiovascular disease among PWH, it remains unknown whether CMV is associated with increased or high-risk coronary plaque. Methods: The Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE) enrolled PWH aged 40–75 years on stable antiretroviral therapy (ART) with low-to-moderate atherosclerotic cardiovascular disease (ASCVD) risk. Among a subset of US REPRIEVE participants, coronary plaque was assessed by coronary computed tomography angiography. Here, we assessed the relationship between CMV immunoglobulin G (IgG) titer and (1) levels of immune activation, (2) inflammatory biomarkers, and (3) coronary plaque phenotypes at study entry. Results: Of 672 participants, mean age was 51 years, 83% were men, median ASCVD risk score was 4.5%, and 66% had current CD4+ T-cell count ≥500 cells/mm 3 . Higher CMV IgG quartile group was associated with older age and lower current and nadir CD4+ T-cell counts. CMV IgG titer was associated with specific inflammatory biomarkers (sCD163, MCP-1, interleukin [IL]-6, hsCRP) in univariate analysis, but not after controlling for HIV-specific factors. In contrast, CMV IgG titer was not associated with coronary artery disease indexes, including presence of plaque, coronary artery calcium (CAC) score >0, vulnerable plaque presence, or Leaman score >5. Conclusions: No meaningful association was seen between CMV IgG titer and coronary artery disease indexes among ART-treated PWH at study enrollment. Longitudinal assessments in REPRIEVE will determine the relationship of CMV IgG titer to plaque progression and cardiovascular events. Clinical Trials Registration: NCT02344290. Abstract : Asymptomatic cytomegalovirus (CMV) infection may be a driver of persistent inflammation in people with human immunodeficiency virus (HIV, PWH) and contribute to cardiovascular disease risk. In this study, CMV immunoglobulin G (IgG) titer was not associated with coronary artery plaque phenotypes at baseline in PWH.